Network admission control solution for 6LoWPAN networks - Oliveira, Luís (2013)
Wireless sensor networks (WSNs) are a technology with high potential to be employed in several industrial and quotidian situations. Self-organization and self configuration are key characteristics of WSNs. In most situations, these characteristics are useful because they minimize the configuration efforts and simultaneously increase the network robustness in case of failures or topology changes. However, they can also be exploited to perform security attacks, since third party nodes can easily join the network and, then, use it to compromise legitimate nodes and to send messages to the Internet. This paper presents a mechanism that can be used to control the nodes that have access to WSNs with 6LoWPAN support. It is based on administrative approval, preventing third party nodes from using the network to communicate with regular nodes. It uses standard protocols which are present in all 6LoWPAN compliant networks, such as 6LoWPAN Neighbor Discover protocol and RPL routing protocol. This paper also presents the design and deployment of a laboratory testbed that validates the proposed solution.